A foundation in agricultural extension science is a prerequisite for agricultural advisors to improve the livelihood of the beneficiaries of their extension and advisory support services in the Western Cape - Levendal, Carol (University of the Free State, 2022)
Agricultural extension is pivotal to transforming the agricultural sector, outlined in many strategic and policy frameworks for South Africa. Therefore, it was necessary to determine what sets apart agricultural advisors who, under the same conditions, have a positive effect on farmers' agricultural output from those who do not. The researcher argues that a foundation in agricultural Extension Science enables the former to improve farmers' livelihoods. Such a study requires comparing agricultural advisors with an Extension Science foundation to an agricultural advisor with no such foundation. Data triangulation methodology was employed. Four data sources were used to determine if there is a difference in the extension and advisory services they provide to farmers in the Western Cape. One data source was measuring the advisor's performance in the field. A performance rating tool was developed to measure how agricultural advisors execute their roles and responsibilities. Hence, criteria for such a tool were necessary. This was developed through reviewing the literature. The agricultural advisors tested these identified roles and responsibilities, and they agreed with them. Through the Log Frame Analysis, managers and specialists from Program 3 in the Western Cape Department of Agriculture examined 11 roles and responsibilities using problem and objective analysis methods. Another data source was the demographics of the agricultural advisor determined through a questionnaire. Two other data sources were the success rate of the farms and the farmers' rating of the advice given by the agricultural advisor taken from the Western Cape Agricultural Land Reform Project Performance Evaluation 2014-2019. The success profiles of the extension advisors were compared to determine if a foundation in Extension Science would improve the farmers' livelihood.
Thesis (Ph.D. (Sustainable Agriculture))--University of the Free State, 2022
Keywords: Agricultural advisors; roles and responsibilities; extension science; extension and advisory services; farmer's livelihood